The digital print : preparing images in lightroom and photoshop for printing - Schewe, Jeff (Peachpit Press, 2014)
Whether you're a digital or a film photographer, you can learn to leverage today's technologies to create masterful prints of your work, and this unique book is devoted exclusively to teaching you how. In it, renowned photographer, educator, and author Jeff Schewe presents targeted chapters on digital printing from Lightroom and Photoshop and shares his expert techniques for optimal output and fine-art reproduction. A companion to The Digital Negative: Raw Image Processing in Lightroom, Camera Raw, and Photoshop, this book teaches you how to take your already perfected images and optimize them for the highest quality final printing. Jeff teaches you about printer types and principles of color management so you get the results you expect. He also shares his strategies on proofing, sharpening, resolution, black-and-white conversion, and workflow, as well as on identifying the attributes that define a perfect print. Learn techniques for optimizing your images for printing Discover how color management can work for you instead of against you Develop an eye for the perfected print.